2017
DOI: 10.1002/ange.201705308
|View full text |Cite
|
Sign up to set email alerts
|

A Carbene Catalysis Strategy for the Synthesis of Protoilludane Natural Products

Abstract: TheA rmillariaa nd Lactariusg enerao ff ungi producet he antimicrobiala nd cytotoxicm ellolide,p rotoilludane,a nd marasmanes esquiterpenoids. We report au nified synthetics trategyt oa ccesst he protoilludane, mellolide, and marasmanef amilieso fn atural products.T he keyf eatureso f theses yntheses are1 )the organocatalytic, enantioselective construction of keyc hirali ntermediates from as implea chiral precursor,2 )the utilityo fakey1 ,2-cyclobutanediol intermediatetoserve as aprecursor to each naturalprodu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…[39] In 2017, Yang and co-workers developed the total synthesis of (-)-pavidolide B (116, Scheme 13), involving an enantioselective organocatalytic cyclopropanation reaction as the key step. [40] They demonstrated that the asymmetric Michael addition/intramolecular-alkylation reaction of dimethyl 2bromo-malonate (108) and hexadienal 109 catalyzed by the amine catalyst (R)-13 led to the cyclopropane derivative 110. Further elaboration of 110 afforded (À )-pavidolide B (116) via a multistep sequence that included the Mitsunobu reaction, an annulation reaction, and the isomerization of the γ,δ-unsaturated enone 115 to the more stable α,β-unsaturated enone 116 (Scheme 13).…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…[39] In 2017, Yang and co-workers developed the total synthesis of (-)-pavidolide B (116, Scheme 13), involving an enantioselective organocatalytic cyclopropanation reaction as the key step. [40] They demonstrated that the asymmetric Michael addition/intramolecular-alkylation reaction of dimethyl 2bromo-malonate (108) and hexadienal 109 catalyzed by the amine catalyst (R)-13 led to the cyclopropane derivative 110. Further elaboration of 110 afforded (À )-pavidolide B (116) via a multistep sequence that included the Mitsunobu reaction, an annulation reaction, and the isomerization of the γ,δ-unsaturated enone 115 to the more stable α,β-unsaturated enone 116 (Scheme 13).…”
Section: Methodsmentioning
confidence: 99%
“…In 2017, Scheidt and co‐workers developed a unified strategy for the enantioselective total synthesis of protoilludane, mellolide, and marasmane families of natural products, in which the NHC‐catalysis played a key role [108] . As shown in Scheme 61, the annulation reaction of acyclic enone‐enal 571 under the catalysis of the N ‐heterocyclic carbene salt 572 led to the formation the vinyl lactone product 573 in a high yield and high stereoselectivities.…”
Section: Applications In Natural Product Synthesismentioning
confidence: 99%
See 3 more Smart Citations